Kualitas Hidup Pasien Diabetes Millitus (DM) dengan Ulkus Diabetikum - Andari, Fatsiwi Nunik; Hamzah, Ahmad Syafwalul; Wahyu, Haifa (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2020)
Diabetes Mellitus (DM) is a non-communicable disease which is projected to experience a significant increase in the world, including in Indonesia. An increase in the population of people with DM has an impact on the increased incidence of diabetic ulcers as a chronic complication of DM. Diabetic ulcers that occur will have an impact on the quality of life of DM sufferers themselves. The purpose of this study was to find out how the quality of life of DM patients with diabetic ulcers. This type of research is a qualitative descriptive study using interview techniques and observational approaches. The number of informants in this study were 5 people. The variables studied were the quality of life of DM patients with diabetic ulcers including physical, functional, psychological and social dimensions. The results of this study generally illustrate that the quality of life of DM patients with diabetic ulcers shows a good category. The quality of life of DM patients on the physical dimension is mostly in the good category (60%), the functional dimension is mostly in the good category (80%), the psychological dimension is mostly in the good category (80%), and the social dimension is mostly in the good category. medium category (40%). It can be concluded that the quality of life of DM patients with diabetic ulcers is generally in the good category. Informants are expected to further improve their quality of life.Â Keywords: Quality of Life, DM, Diabetic Ulcer